RETRACTED: The Variation of Nasal Microbiota Caused by Low Levels of Gaseous Ammonia Exposure in Growing Pigs - Wang, Tongxin; He, Qiongyu; Yao, Weilei; Shao, Yafei; Li, Ji; Huang, Feiruo (Frontiers in Microbiology, 2019)
Exposure to gaseous ammonia, even in low levels can be harmful to pigs and human health. But less is know about how sustained gaseous ammonia affect nasal microbiota colonization in growing pigs. A total of 100 pigs were housed in 20 separate chamber and exposed continuously to gaseous ammonia at either 5, 10, 15, 20, 25 ppm (four groups per exposure level) for 4 weeks. The results of nasal microbiota showed that the increase of ammonia concentration decrease the alpha diversity and relative abundance of nasal microbiota, especially in 20 and 25ppm. Proteobacteria, Firmicutes, Bacteroidetes, Actinobacteria and Chloroflexi were the most abundant phylum. In addition, relative abundances of 24 microbial genera significantly changed as the ammonia level increase, 4 microbial genera (Pseudomonas, Lactobacillus, Prevotella, Bacteroides) significantly decreased at 25ppm, while only two genera (Moraxella and Streptococcus) increased at 25ppm. The PICRUSt analyses showed that the relative abundances of the nasal microbiota involved in cell motility, signal transduction, nervous system, environmental adaptation, and energy and carbohydrate metabolism were significantly decreased, while genes in immune system, endocrine system, circulatory system, immune system diseases and metabolism of vitamins, lipid, and amino acids were increased as the ammonia level increase. The results in vivo showed that the increase of ammonia level can cause respiratory tract injury and increase the number of Moraxella and Streptococcus species, while decrease respiratory immunity and growth performance, especially at the ammonia level of 25ppm, consistent with the proliferation of harmful bacteria in nasal microbiota analysis.